DNA barcoding and diversity analysis of 19 economically important Philippine sea cucumbers (Holothuroidea) - Alcudia-Catalma, Ma. Neda; Tecson-Mendoza, Evelyn Mae; Laurena, Antonio C.; Ocampo, Pablo P.; Garcia, Roberta N.; Diaz, Maria Genaleen Q. (2020)
This study established the DNA barcodes of 19 economically important Philippine sea cucumbers belonging to Class Holothuroidea under Phylum Echinodermata using the cytochrome c oxidase I (COI) gene. These include sea cucumbers from the Family Holothuriidae under Order Aspidochirotida: Bohadschia marmorata, B. koellikeri, B. vitiensis, B. argus, Bohadschia sp. 1, Actinopyga echinites, A. lecanora, Holothuria scabra, H. fuscogilva, H. atra, H. impatiens, and H. albiventer; from the Family Stichopodiidae under Order Aspidochirotida: Stichopus horrens, S. monotuberculatus, S. vastus, S. hermanni, S. chloronotus, and Thelenota ananas; and from the Family Phyllophoriidae under Order Dendochirotida was Neocucumis proteus. Based on Kimura-2 pairwise (K2P) distances, low genetic variation within species of 0.005?0.018 was observed except for several species such as S. chloronotus, H. albiventer, A. echinites, and H. scabra ? which had 0.057, 0.181, 0.207, and 0.215 within-species genetic variations, respectively. On the other hand, variation between species within a genus was 0.123 for Bohadschia, 0.18 for Actinopyga, 0.19 for Holothuria, and 0.071 for Stichopus. Phylogenetic tree using neighbor-joining analysis showed monophyletic clades for the genera Bohadschia, Actinopyga, Stichopus, Thelenota, and Neocucumis while paraphyletic clade was formed for the genus Holothuria. COI DNA sequences and barcodes were established for the first time for Neocucumis proteus and Holothuria albiventer. (Author's abstract)